Factors Affecting Customer Purchase Interest In Veteran Jaya Furniture Shop - Tina Muhardika Handayani; Muammar Rinaldi (Jurnal Manajemen Bisnis Eka Prasetya, 2023)
This study aims to determine the effect of promotion on buying interest in the Veteran Jaya Furniture Shop, knowing the effect of discounts on buying interest in the Veteran Jaya Furniture Shop, knowing the effect of brand image on buying interest at the Veteran Jaya Furniture Shop. Knowing the effect of promotions, discounts, and brand imagery on buying interest at the Veteran Jaya Furniture Shop. The research methodology used is a quantitative descriptive method. The type of data used in this study is quantitative data, which is data obtained in the form of numbers or numbers. Data sources in the form of primary data and secondary data. Primary data obtained from the results of the distribution of questionnaires to respondents, secondary data obtained from data and literature relating to the problems discussed. The population in this study was all consumers who made a purchase at Veteran Jaya Furniture during the 2020 period of 7,125 consumers. By using the Slovin formula with an error rate of 10%, the number of samples is 100 respondents. Data were analyzed using multiple linear regression analysis methods. The analysis results provide an equation of buying interest = 8.065 + 0.242 promotion + 0.213 discounted price + 0.190 brand image + e.